Incentives and Creativity in Groups - Joachim Ramm; Sigve Tjøtta; Gaute Torsvik (Center for Economic Studies and ifo Institute (CESifo), 2013)
It has been argued that monetary incentives restrain individual creativity and hamper performance in jobs requiring out of the box thinking. This paper reports from an experiment designed to test if the negative incentive effect is present also when individuals work together to solve such problems. We do not find a negative impact of incentives on group performance. As a comparison we ran the same experiment (the Candle Problem) with and without incentives for individuals as well. Incentives did not reduce performance there either. Comparing individuals with groups we find that team-work facilitates creative problems solving. Individuals appear to be more creative when working together than when working alone.
Keywords: J24; J31; O31; M11; 330; incentives; innovation; creativity